AN EVALUATION OF THE BOOK LAUDATO SI FROM THE SEVENTH-DAY ADVENTIST CHURCH PERSPECTIVE - Kelendonu, Michael Andrew; Pasuhuk, Suryanica Aristas (Klabat Theological Review; Vol 4 No 1 (2024): Klabat Theological ReviewDO - 10.31154/ktr.v4i1.1136.13-25, 2024)
Laudato Si, which translates to "Praise to be you," is a Latin expression. The work of literature Laudato Si by Pope Francis, primarily centers on the existence of an ecological concern. The scripture foretells that the mark of the beast will be given to those who refuse to worship God on the final day and are “united.” One approach that does not generate much debate for starting "the efforts to establish a one-world government" is the treatment of environmental issues. This book implies several things, including the necessity of Sunday being a rest day, honoring Mary especially, and redemption via deeds, to bring humanity together while addressing environmental challenges. By giving Laudato Si a critical evaluation, readers can bring attention to contemporary challenges like ecological issues that have theological implications for the church and society, completing the eschatological perspective of the end times. Keywords: Laudato Si, Ecological issue, Sunday, Eschatological.